Revitalizing Islamic Religious Education Curriculum in the Digital Era: A Philosophical Reflection of Sayyed Hossein Nasr and Yasraf Amir Piliang - Achmad Fatih Mubarok; A. Zuhdi; Sutiah Sutiah (Peradaban Journal of Interdisciplinary Educational Research, 2025)
Islamic Religious Education (IRE) in higher education continues to face serious challenges due to the dominance of normative-doctrinal approaches that are less adaptive to the complexities of the digital era. This study aims to formulate a transformational IRE curriculum based on the philosophy of knowledge that can address both the spiritual crisis and technological disruption. Employing a qualitative approach, the research applies an in-depth literature analysis of the works of Seyyed Hossein Nasr and Yasraf Amir Piliang, contextualized within the condition of IRE curricula in Indonesia. The findings reveal that Nasr’s concept of sacred knowledge provides a transcendental framework for strengthening spirituality, while Piliang’s critique of the culture of simulacra offers a critical lens to understand the impact of digitalization on education. Synthesizing these perspectives produces a transformational curriculum model that integrates religious, philosophical, and digital dimensions, while maintaining a balance between perennial values and contemporary needs. This study concludes that developing a transformational IRE curriculum is not only urgent but also strategic for enhancing the competitiveness of Islamic education in the global era. Its practical implication is that the curriculum should be directed toward integrating Islamic epistemology, digital literacy, and participatory pedagogical methods that foster both critical awareness and profound spirituality. Pendidikan Agama Islam (PAI) di perguruan tinggi masih menghadapi tantangan serius akibat dominasi pendekatan normatif-doktrinal yang kurang adaptif terhadap kompleksitas era digital. Penelitian ini bertujuan untuk merumuskan konsep kurikulum transformasional PAI berbasis filsafat ilmu yang mampu menjawab krisis spiritual sekaligus disrupsi teknologi. Penelitian menggunakan pendekatan kualitatif dengan analisis kepustakaan mendalam terhadap karya Seyyed Hossein Nasr dan Yasraf Amir Piliang, yang kemudian dikontekstualisasikan dengan kondisi kurikulum PAI di Indonesia. Hasil penelitian menunjukkan bahwa pemikiran Nasr tentang pengetahuan sakral (sacred knowledge) menawarkan kerangka transendental bagi penguatan spiritualitas, sementara gagasan Piliang mengenai budaya simulakra memberikan lensa kritis untuk memahami dampak digitalisasi terhadap pendidikan. Sintesis keduanya menghasilkan model kurikulum transformasional yang mengintegrasikan dimensi religius, filosofis, dan digital, sekaligus menekankan keseimbangan antara nilai-nilai perennial dan kebutuhan kontemporer. Penelitian ini menyimpulkan bahwa pengembangan kurikulum PAI yang berorientasi pada transformasi tidak hanya mendesak, tetapi juga strategis bagi penguatan daya saing pendidikan Islam di era global. Implikasi praktisnya, kurikulum perlu diarahkan pada integrasi epistemologi Islam, literasi digital, dan metode pedagogis partisipatif yang menumbuhkan kesadaran kritis sekaligus spiritualitas mendalam.